2015
DOI: 10.2967/jnumed.114.149609
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of 99Mo/99mTc Separation: Non–Fission Reactor Production of 99Mo as a Strategy for Enhancing 99mTc Availability

Abstract: This paper discusses the benefits of obtaining 99m Tc from non-fission reactor-produced low-specific-activity 99 Mo. This scenario is based on establishing a diversified chain of facilities for the distribution of 99m Tc separated from reactor-produced 99 Mo by (n,γ) activation of natural or enriched Mo. Such facilities have expected lower investments than required for the proposed chain of cyclotrons for the production of 99m Tc. Facilities can receive and process reactorirradiated Mo targets then used for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Pasha and Narayana (2007) as well as our previous study obtained coefficient correlation of 0.995 (Pillai et al, 2014). The difference between both the present and previous one is not significant, and the coefficient correlation of present method is sufficient for NaOCl concentration measurement.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Pasha and Narayana (2007) as well as our previous study obtained coefficient correlation of 0.995 (Pillai et al, 2014). The difference between both the present and previous one is not significant, and the coefficient correlation of present method is sufficient for NaOCl concentration measurement.…”
Section: Resultssupporting
confidence: 46%
“…The range of the linearity is wider than previous developed method. Pasha and Narayana (2007) reported the linearity was (Abdulrahman & Basavaiah, 2012), whereas in the previous study, we reported the linearity was in the range of 0.19-2.25 mg L -1 (Pillai, Dash, & Knapp, 2014). Actually, there is no guideline which shows a limitation of NaOCl concentration in parenteral pharmaceuticals.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…About 0.9 million diagnostic procedures (2,750 procedures/day) have been performed every year using 99m Tc radiopharmaceuticals with an average dose of about 740 MBq (20 mCi) at the time of injection to a patient: 2.05 TBq (55 Ci) of 99m Tc is used every day. The activity of 99m Tc needed in Japan every day at a radiopharmaceutical company to prepare 99m Tc radiopharmaceuticals is calculated to be 4.10 TBq (110 Ci) by referring to the reports by Pillai et al, 38) Bennett et al, 39) and Ross et al 40) as follows. In the U.S.A., about 50,000 diagnostic procedures are carried out daily using 99m Tc radio-pharmaceuticals.…”
Section: Capability To Meet Demand Formentioning
confidence: 99%
“…R. A. Pillai, Dash, and Knapp 2013). Mo is obtained from natural Molybdenum (MoO 3 ) irradiated by either cyclotron or research reactor (M. R. a Pillai, Dash, and Knapp 2015;Selivanova et al 2016;Amin et al 2014). The advantages of nonfission 99 Mo compared to fission 99 Mo are the easy handling of the waste, the low radioactivity waste, and the simple post-irradiation method.…”
Section: Development Of New Materials Formentioning
confidence: 99%